Integrasi Pendidikan Berpusat pada Anak dan Kesetaraan Gender dalam Kerangka Pendidikan Islam: Analisis Konseptual Humanistik-Profetik - Asma'I Gunarsih; Akbar Yusgiantara; Rustam Ibrahim (AHKAM, 2025)
Although child-friendly education and gender equality have been widely examined, studies that specifically address the integration of these two concepts within the framework of Islamic education remain limited. This study aims to examine the normative foundations, pedagogical significance, and practical implications of integrating child-friendly education and gender equality within Islamic education. It employs a qualitative methodology based on a literature review and content analysis of primary and secondary sources, including scholarly literature, policy documents, and recent Islamic studies relevant to educational environments. The findings indicate that the principles of rahmah (compassion), karāmah al-insāniyyah (righteous deeds), and al-‘adl (justice) function as fundamental pillars for realizing non-repressive and gender-equitable education, such that their integration fosters a safe, inclusive, and humanistic learning environment. These findings broaden understanding of prophetic Islamic pedagogy and offer a conceptual framework for educational institutions to reformulate their curricula and teaching methodologies. The study also opens prospects for further inquiry through field studies and longitudinal approaches to evaluate the effectiveness of this integrative paradigm in contemporary Islamic educational practice.